Van der Waals enhanced interfacial interaction in cellulose/zinc oxide nanocomposite coupled by graphitic carbon nitride. (15th September 2021) - Wang, Xin-Yu; Wang, Yan; Zhao, Nian-Dan; Zheng, Ming; Guo, Yuan-Ru; Pan, Qing-Jiang
Abstract: In-depth understanding of interfacial property is the key to guiding the synthesis of biomass composites with desired performance. However, the exploration is of great challenge due to limitations of experimental techniques in locating hydrogen, requiring large/good crystals and detecting a weak interaction like van der Waals (vdW). Herein, we experimentally and computationally investigated the composite cellulose/zinc oxide/g-C3 N4 . Hydrothermal synthesis afforded cellulose/ZnO, and then fabricated the ternary composite by adding g-C3 N4 under ultrasonic condition. Three components are found to co-exist in the composite, and the ZnO nanoparticle is attaching to cellulose and coupling with g-C3 N4 . These experimental findings were corroborated by relativistic DFT calculations. The interfacial coupling is elaborated as contributions of dative bonds, hydrogen bonds and vdW interaction. The vdW is increased by a factor of 4.23 in the ZnO/g-C3 N4 interface. This improves electron-hole separation and offers prospective application of the composite in photocatalysis, antibacteria and gas sensing. Graphical abstract: Three components co-exist in the composite, corroborated by DFT calculation. The interfacial coupling is elaborated as dative/hydrogen bonds and van der Waals interaction. The last one is greatly increased by a factor of 4.23 in the two-dimension g-C3N4-involved interface. Unlabelled Image Highlights: Three components are found to co-exist in the composite. Experimental finding is corroborated by DFT calculation. Interfacial coupling is elaborated as dative/hydrogen bonds and van der Waals. The vdW is increased by a factor of 4.23 in the 2D g-C3 N4 -involved interface. Chemical interfacial coupling helps to improve the catalytic performance.